Kegiatan Majelis Taklim Rahmatan Lil Alamin dalam Mendukung Pendidikan Agama di Masyarakat - Wirdati, Wirdati; Rivauzi, Ahmad; Nurjanah, Nurjanah; Halomoan, Halomoan (Prodi Pendidikan Keagamaan Islam, 2025)
The existence of the Majelis Taklim as a non-formal religious education institution is still not functioning well. However, the Majelis Taklim of the Rahmatan Lil Alamin Mosque has attempted to teach religion more comprehensively by making the mosque the basis for all community activities. This can support the spirit of the Smart Surau program launched by the Padang City Government. This article describes how the Majelis Taklim activities of the Rahmatan Lil Alamin Mosque and how it is likely to succeed the Smart Surau program in realizing the vision of Padang CityThe method used is qualitative with a case study and sustainability analysis to be able to support the Smart Surau program. Informants consisted of the head of the Majelis Taklim, mosque administrators and the head of the neighborhood association (RT). Through in-depth interviews, participatory observation and documentation, data were collected then analyzed using an interactive model Technical triangulation was used to validate the data. The results showed that the activities of the majelis taklim included routine monthly study sessions, blessed Fridays, blessing clean-up sessions, Qur'an recitation, dawn warriors, Umrah savings, a thousand-a-day dawn alms, assistance to orphans and the poor, a marketing cooperative, Islamic holiday takmirs and a Blessed Kitchen outlet. These activities restored the spirit of the Surau Saisuak. In the future, the majelis taklim can support the smart surau program for the sustainability of comprehensive dawn in the context of Islamic religious education for the community.